Tracking suspended particulate organic matter biochemistry from glacial meltwater runoff to coastal waters of an Antarctic fjord - Parodi Calo, Claudia (2024)
Increased glacier melting runoff in Antarctica involves intensification of freshwater, nutrients, sediments and organic matter inputs from land to the sea, which is impacting coastal ecosystems. Basic environmental characteristics of water and biochemical composition of suspended particulate organic matter (POM) both in the proglacial melting runoff system (PROGLARS) of Collins Glacier and marine surface waters of Collins Bay was studied based on organic biopolymers and molecular level analysis of amino acids (AAs), to discern among sources and degradation state in the two environments. Hierarchical Clustering Analysis revealed that PROGLARS stations and marine stations form two distinct groups in terms of water physicochemical characteristics and suspended POM biochemical composition. These differences are the consequence of low restricted contribution of freshwater from Collins Glacier runoff into the coastal-marine environment. Our results evidenced low concentrations of terrestrial suspended POM in marine waters of Collins Bay mainly attributed to low meltwater inputs between the 1st and 7th of February 2018. In terms of macromolecular composition, the predominance of proteins, denote the labile nature of suspended POM in the two environments. Suspended POM in Collins Bay is labile, poorly degraded, representing a protein supplemented food resource, with high energetic value and easily assimilated by heterotrophic marine organism. AAs composition supported less degraded suspended POM derived from marine phytoplankton in surface waters of Collins Bay, whereas, great degradation of suspended POM in the proglacial runoff system of Collins Glacier. Changes in the biochemistry of suspended POM caused by glacial melting and retreat, may affect food features and availability, the productivity of ecosystems, and ultimately, the capacity of Antarctic fjords to act as carbon sinks and climate regulators. Considering low influence of Collins Glacier meltwater in coastal marine waters of Collins Bay, due to the relatively slow retreat of Collins Glacier and low development of its meltwater runoff system, the results of our work are relevant as baseline information for comparison with other Antarctic fjords. Further knowledge about meltwater runoff and suspended POM input dynamics in Antarctic coastal ecosystems, is critical, particularly in areas prone to undergo increased glacier melting in the following decades.